Green synthesis and multifaceted applications: challenges and innovations in carbon dot nanocomposites - S. Varadharajan; Kirthanashri S. Vasanthan; Vidhi Mathur; N. Hariperumal; Nirmal Mazumder (Discover Nano)
Abstract This paper describes the potential of carbon dot nanocomposites (CDs) synthesized from waste materials by top-down and bottom-up state-of-the-art approaches. Through sustainable practices, wastes are converted into valuable nanomaterials, solving environmental problems and pioneering advances in nanotechnology. In this paper, an overview of the synthesis aspects of CDs is presented with the formation of their versatile nanocomposites and metal/metal oxide elements. The phase of this paper has been devoted to elaborate study of the multifaceted applications of CDs in various sectors, ranging from electronics and biomedicine to environmental remediation. Although having huge potential, CDs application is presently hampered due to limitations on scalability, stability, and reproducibility. In this review paper, most profound insights have been drawn into overcoming these barriers for clear routes toward future innovations. The present research being undertaken in this area has, therefore, underscored sustainable nanotechnology to resolve global problems and achieving technological development through green synthesis. Necessitating the efficient sewage disposal systems ensuring minimum toxin generation. Graphical abstract